Rapid Generation and Detection of Biomimetic Oxygen Concentration Gradients In Vitro. Issue 1 (December 2017) - Khan, Daud; Roberts, Steven; Cressman, John; Agrawal, Nitin
Abstract Hypoxic regions exist within most solid tumors and often lead to altered cellular metabolism, metastasis, and drug resistance. Reliable generation and detection of biomimetic gaseous gradientsin vitro is challenging due to low spatiotemporal resolution and poor longevity of gradients utilizing microfluidic techniques. Here, we present a novel and simplistic approach for producing gradients of dissolved oxygen (DO) within a lab-on-a-chip platform. Linear and stable DO gradients with high spatial resolution are established by introducing pre-gassed media into the gradient generating network. An underlying platinum(ii) octaethlporphyrin ketone (PtOEPK) based sensor layer allows parallel detection of oxygen. A thin 3-sided glass coating on the inner channel walls prevents multi-directional diffusion of ambient oxygen across PDMS preserving the gradient resolution and stability. Viability analysis of normal mammary epithelial cells (MCF-12A) under oxygen gradients revealed 70% mortality after 6 hours of hypoxic exposure. Biological applicability of the platform was further validated by demonstrating increase in endoplasmic reticulum stress of MDA-MB-468 cells with time and with increasing oxygen tension. The unique ability to establish parallel or opposing gradients of gases and chemicals offers the potential for a wide range of applications in therapeutic development, and fundamental understanding of cellular behavior during hypoxia.